“A knife sharp enough to divide us”: William H. Seward, Abraham Lincoln, and black colonization - Page, S (Oxford University Press, 2016)
This article explores William H. Seward's opposition to Abraham Lincoln's pursuit of black colonization (resettlement) during the American Civil War. Although the existing literature has shown a cursory awareness of the two men's differences over that policy, scholars have failed to appreciate the full force of what was easily the strongest point of disagreement between the president and his secretary of state. Drawing on archival research from three countries, this article explains why Seward opposed colonization. It charts how wartime colonization policy evolved and investigates why even Seward could discern some merit in the idea during the early part of the war. Above all, it demonstrates the dilemmas faced by a would-be saboteur of the presidential will, as well as the unintended consequences that can arise from an administrator's well-meaning interventions in policymaking.